Cardiogeneticsbank@UZA: A Collection of DNA, Tissues, and Cell Lines as a Translational Tool - Alaerts, Maaike; van de Beek, Gerarda; Luyckx, Ilse; Meester, Josephina; Schepers, Dorien; Verstraeten, Aline; Saenen, Johan; Van Craenenbroeck, Emeline; Goovaerts, Inge; Rodrigus, Inez; Laga, Steven; Hendriks, Jeroen; et al. (Frontiers in Medicine, 2019)
Cardiogeneticsbank@UZA is an academic hospital integrated biobank that collects aortic tissue, blood, cell lines (fibroblasts, vascular smooth muscle cells, peripheral blood mononuclear cells and induced pluripotent stem cells) and DNA from patients with cardiogenetic disorders, for both diagnostic and research purposes. We adhere to a quality management system and have established standard protocols for the sampling and processing of all cardiogenetic patient related materials. Cardiogeneticsbank@UZA is embedded in the Biobanking and Biomolecular Resources Research Infrastructure Belgium (BBMRI.be) and samples from this biobank are available for commercial and academic researchers, through an established access procedure. Currently, the extremely valuable cardiogenetics collection consists of more than 8700 DNA samples, 380 tissue samples and 500 cell lines of 7578 patients, and is linked with extensive clinical data. Some interesting potential research applications are discussed.